Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Sains Melalui Metode Eksperimen Siswa Kelas IV SDN Kayumpia Kecamatan Kinovaro - Pinus, Pinus; Ramadhan, Achmad; Haerudin, Haerudin (Jurnal Kreatif Online, 2018)
The main problem of this research is the result of the student grade IV SDN Kayumpia to learn science program is to low. The peroblem statement of this research is an experiment method apllycan be increase the result of student to learning science. The goal of the research is to description of experiment method can be increase the abilty of the student grade IV SDN Kayumpia. Kind of this research is an action class research which did in two siclus. Designed by Kemmis and Mc.Taggart. The research did through view they are planning, action, observation, and reflectionn. The subject of this research are fiveteen student of student of SDN Kayumpia. The result of teacher observation for the first siclus got 55% and second siclus got 90%. The result of teacher observation for the first siclus got the grade 46,7% it mean failed and the second siclus got the grade 91,1%. Student result for the resultfor the first siclus is 60% and for the second siclus got 93,3%. It mean teaching method of second siclus got good indicator of the research wich found 85%, it can be conclude that eksperiment method apply can be increase the result of student grade IV to learning science subject at SDN Kayumpia. Keywords: Result of Studying, Science, Eksperiment